Preparation method of ardealite composite nano adhesive material
Through ultrasonic dispersion and surface modification technology, combined with hot air circulation curing, the problems of phosphogypsum composites in nanoparticle dispersion, interface bonding and curing uniformity are solved, and the mechanical properties and high temperature resistance of the material are significantly improved.
Patent Information
- Application Number
- CN202510166794.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing phosphogypsum composite materials have shortcomings in nanoparticle dispersion, interface bonding force and curing uniformity, resulting in limited improvement in mechanical properties and insufficient heat resistance and corrosion resistance.
The dual technology of ultrasonic dispersion and surface modification is adopted. Through the optimized ratio of modified adhesives and dispersants, the uniform dispersion and interface bonding of nanoparticles in the phosphogypsum matrix is ensured, and the overall stability and strength of the material are ensured in combination with hot air circulation and curing technology.
It significantly improves the mechanical properties of composite materials, especially compressive and tensile strength, improves high temperature resistance and aging resistance, and ensures the stability and toughness of the material in extreme environments.
Smart Images

Figure CN119899616A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials and environmentally friendly materials, and in particular to a method for preparing a phosphogypsum composite nano adhesive material. Background Art
[0002] With the increasing demand for environmental protection and sustainable development, phosphogypsum, as an industrial waste, has gradually been applied to the fields of construction and environmental protection, especially in the preparation of composite materials. Phosphogypsum composite materials have good light weight, heat insulation, sound insulation and other properties, and are widely used in building repairs and the manufacture of environmentally friendly materials.
[0003] In the prior art, the preparation of phosphogypsum composite materials mostly relies on traditional mechanical stirring methods and simple hot pressing molding technology. These methods can effectively produce phosphogypsum composite materials and improve their mechanical properties, wear resistance, etc. The introduction of nanomaterials provides a new idea for enhancing the performance of materials, especially in terms of improving strength, toughness and corrosion resistance.
[0004] However, there are still some deficiencies in the existing technology, especially in the dispersion of nanomaterials, uniformity of composite materials and heat resistance. The problems are particularly prominent. First, the existing technology usually adopts a simple stirring method to disperse nanoparticles, which makes the nanoparticles often aggregate in the composite materials, affecting the improvement of mechanical properties. Secondly, although the traditional surface modification method improves the bonding between nanoparticles and the matrix to a certain extent, the modification effect is usually limited, and it is difficult to ensure the stability of the particles under extreme conditions. In addition, the existing curing method also has obvious deficiencies in ensuring the stability of the material. The static heating curing process is prone to uneven curing, bubbles or cracks, thereby affecting the overall strength and durability of the composite material. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a phosphogypsum composite nano-adhesive material, which solves the problems of the existing phosphogypsum composite materials in terms of nano-particle dispersibility, interface bonding strength and curing uniformity.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: a phosphogypsum composite nano-adhesive material, the phosphogypsum composite nano-adhesive material comprising the following components in parts by weight: Phosphogypsum powder: 70-90 parts. The main component of phosphogypsum is CaSO4·2H2O. The presence of water in it enables phosphogypsum to provide a better hydration reaction interface when combined with adhesives. After crushing and screening, the specific surface area of phosphogypsum increases, thereby increasing its contact area with nanomaterials and adhesives and enhancing the adhesion of composite materials; Nanomaterial: 5-15 parts, wherein the nanomaterial is nano-silicon dioxide, nano-silicon nitride or a combination thereof. The tiny size of the nanomaterial gives it a high specific surface area, which helps it to be evenly dispersed in the composite material and strengthen the bonding force with the matrix. Among them, nano-silicon dioxide has a high surface energy and can form a strong interface with phosphogypsum, thereby improving the compressive, tensile and flexural strength of the composite material, while nano-silicon nitride can provide stronger heat resistance and oxidation resistance, and improve the stability of the composite material in a high temperature environment; Modified adhesive: 5-10 parts. The mechanism of action of the modified adhesive is to form a strong chemical bond or cross-linking structure through a chemical reaction between the active groups in its molecular structure and the hydroxyl groups or surface water molecules on the surface of phosphogypsum; Surfactant: 0.5-3 parts, wherein the surfactant is a silanizing agent, an aminating agent or a combination thereof, and the surfactant forms an adsorption layer with the surface of the nanoparticles through its polar and non-polar parts, thereby reducing the mutual attraction (such as van der Waals force) between the nanoparticles, thereby effectively preventing the agglomeration of the particles; Dispersant: 0.5-2 parts. The main function of the dispersant is to adjust the interaction between particles by changing the charge or polarity on the surface of nanoparticles. The dispersant can effectively reduce the attraction between particles and prevent particle agglomeration by adsorbing on the surface of particles to form a stable charge layer or hydrophobic layer.
[0007] Preferably, the modifier is a silanizing agent, and the reaction conditions are: The concentration of the silanizing agent is 2% to 5%. The silane molecule has two important parts: one is the silane group that can react with the surface, and the other is the functional group that can form chemical bonds with other molecules. In the concentration range of 2% to 5%, the silane molecules can effectively adsorb on the surface of the nanoparticles to ensure the uniformity and stability of the modified layer; The reaction temperature is 25℃~60℃, which is the most suitable condition. Too low temperature will lead to slow reaction speed and ineffective surface modification; too high temperature will cause the silanization agent to degrade or volatilize, resulting in incomplete reaction, thus affecting the final surface modification effect. The reaction time is 1 to 3 hours. If the reaction time is too short, the silane groups will not be able to fully contact and adhere to the particle surface, resulting in insufficient modification. On the contrary, if the reaction time is too long, it will lead to over-reaction or by-product generation. Therefore, this reaction time helps the silanization agent to react optimally with the surface, ensuring that the modified layer is uniform and stable. The solvent is ethanol or water. Ethanol, as a weaker polar solvent, helps to dissolve silane molecules and promote the reaction of the silanizing agent; water can react with the hydrolyzed groups in the silanizing agent to form hydroxyl groups that can react with the surface of the nanoparticles.
[0008] The present invention also provides a method for preparing a phosphogypsum composite nano adhesive material, which is characterized by comprising the following steps: S1. Surface modification of nanomaterials; S2. pretreating phosphogypsum powder; S3, mixing the surface-modified nanomaterial with phosphogypsum powder, adhesive and other additives; S4, forming the mixture; S5. Curing the formed composite material.
[0009] Preferably, the surface modification of the nanomaterial comprises: The nanomaterial is modified using a modifier, wherein the modifier is a silanizing agent. The silanization reaction is a reaction between a silane group (such as 3-aminopropyltriethoxysilane) and a hydrophilic functional group (such as a hydroxyl group) on the surface of the nanoparticle to form a covalent bond. In this way, the silanizing agent introduces active groups into the surface of the nanoparticle, thereby enhancing the interfacial bonding force between the particle and the matrix material, and improving the mechanical properties and bonding strength of the composite material; Dissolve the nanomaterial and the modifier in an appropriate amount of solvent, and perform ultrasonic treatment to ensure that the modifier is evenly attached to the surface of the nanomaterial, wherein the ultrasonic dispersion time is 15 minutes to 30 minutes, and the ultrasonic power is 50W to 200W. This time and power can not only promote the reaction between the silanizing agent and the functional groups on the surface of the nanoparticles, but also disperse the particles to prevent agglomeration between the particles. The shear force generated by the ultrasonic wave helps to overcome the van der Waals force and electrostatic effect between the nanoparticles, so that the particles are evenly dispersed in the solution, ensuring that the modifier can evenly attach to the surface of each nanoparticle; The surface-modified nanomaterials are dried within a temperature range of 30°C to 80°C to remove excess solvent and unreacted chemicals. Too high a drying temperature will cause decomposition of the modifier or incomplete reaction, thus affecting the modification effect; while too low a temperature will make it difficult to completely remove the solvent, resulting in residual solvent or chemicals on the surface of the nanoparticles, which will in turn affect the subsequent material properties. Therefore, this temperature range can ensure the stability and uniformity of the surface modification layer of the nanoparticles.
[0010] Preferably, the pretreatment of the phosphogypsum powder comprises: The phosphogypsum powder is dried to ensure that its moisture content is less than 1%. The main component of phosphogypsum is CaSO4·2H2O. The crystal water and free water in it will affect the curing of the adhesive and the compatibility of phosphogypsum in the composite material. The drying process evaporates the water by heating, reduces the inhibitory effect of water on the reaction, improves the activity of the phosphogypsum surface, and promotes its combination with other materials (such as adhesives and nanomaterials). When the moisture content is less than 1%, phosphogypsum can react with the adhesive more effectively to form a strong connection, thereby improving the bonding strength and mechanical properties of the composite material; The dried phosphogypsum powder is crushed to less than 200 meshes to increase its surface area. The main function of the crushing process is to increase the specific surface area and reactivity of the particles. The larger the surface area of the phosphogypsum powder, the larger the contact area with the adhesive and nanomaterials, thereby improving the interfacial compatibility. Finer particles are conducive to increasing the density of the composite material and improving the mechanical properties of the material; The crushed phosphogypsum powder is screened to remove larger particles to ensure uniformity. Through screening, the particle size is uniformed, ensuring that the components can be evenly distributed during the molding and curing process of the composite material, thereby improving the overall performance of the final material. At the same time, uniform particle size can avoid mechanical defects caused by excessively large particles, such as stress concentration, and improve the structural integrity and durability of the material.
[0011] Preferably, the mixing process of the mixture comprises: The surface-modified nanomaterials are mixed with phosphogypsum powder in proportion. After the surface of the nanomaterials is modified, they can better combine with the phosphogypsum particles. This is mainly due to the chemical reaction between the functional groups on the surface of the nanomaterials and the functional groups (such as hydroxyl groups) on the surface of the phosphogypsum. Through this mixing, the nanoparticles are evenly distributed in the phosphogypsum matrix, thereby achieving the goal of enhancing the overall mechanical properties of the material. Adding modified adhesive and surfactant to the mixture, the hydrophilic groups of the surfactant interact with the hydrophilic groups on the surface of the nanoparticles to stabilize the particle surface, prevent agglomeration, and improve the uniformity and stability of the composite material; Adding dispersants to enhance the dispersibility of nanomaterials in the mixture. Dispersants adsorb on the surface of nanoparticles to reduce the attractive forces between particles (such as electrostatic forces and van der Waals forces), thereby preventing particle agglomeration. The mixture is stirred by ultrasonic dispersion to make it evenly dispersed and ensure the uniform distribution of nanoparticles. Under the action of ultrasound, the bubbles in the solution will continue to expand and burst, thereby effectively preventing the agglomeration of particles. In addition, the cavitation effect of ultrasound can make the tiny bubbles in the solution disappear quickly, further promoting the uniform dispersion of particles in the matrix. This process can greatly improve the dispersibility of nanoparticles in a short period of time and ensure the uniformity and stability of the composite material.
[0012] Preferably, the molding process includes: After the mixture is poured into the mold, it is molded by compression molding or hot pressing. The compression molding pressure range is 0.5MPa to 2MPa, the hot pressing molding pressure range is 2MPa to 5MPa, the molding temperature range is 20℃ to 120℃; the molding time is 30 minutes to 90 minutes. The pressure in this compression stage is relatively small, which is mainly used to initially compact the composite material to ensure its shape stability and avoid large-scale material deformation. In this hot pressing stage, higher pressure and appropriate temperature are used to promote the cross-linking and curing of the adhesive, further improving the mechanical strength and stability of the composite material. Hot pressing can cause the molecular chains to cross-link at high temperatures to form a more solid network structure. The formed composite material is cooled to fix its shape.
[0013] Preferably, cooling the formed composite material comprises: Cooling temperature range: 25℃~40℃, this temperature range can prevent uneven stress on the surface and inside of the material, thereby avoiding warping or cracking of the material; Cooling time: 1 hour to 4 hours. Too fast cooling will cause a large temperature difference between the surface and the inside, resulting in increased internal stress, while too long cooling time will affect production efficiency. Therefore, this cooling time can ensure the shaping effect of the composite material and optimize its performance.
[0014] Preferably, the curing process comprises: The formed composite material is placed in a curing oven for heating and curing. The curing process mainly depends on the cross-linking reaction of the adhesive. Under heating conditions, the active groups (such as hydroxyl, amino, epoxy, etc.) of the molecular chain of the adhesive (such as epoxy resin, polyurethane, etc.) will undergo chemical reactions to form covalent bonds or physical bonds, gradually forming a three-dimensional cross-linked network structure; The curing temperature is controlled between 60℃ and 120℃. A lower temperature (such as 60℃) helps a slow and uniform curing process and avoids the internal stress or crack formation caused by too fast curing. A higher temperature (such as 120℃) can accelerate the cross-linking reaction and shorten the curing time, which is suitable for production processes with high time requirements. However, too high a temperature will cause the adhesive to degrade or over-react, resulting in uneven curing. Therefore, the curing temperature needs to be precisely controlled within the range of 60℃ to 120℃ to ensure that the adhesive can be fully cross-linked under optimal conditions to obtain a stable three-dimensional network structure. The curing time is controlled between 2 hours and 5 hours. If the time is too short, the cross-linking will be incomplete, affecting the strength and stability of the final material. Although a long time can enhance the degree of cross-linking, it will also cause stress inside the material and even cause excessive cross-linking of the adhesive, affecting the toughness of the material. Therefore, this curing time range can ensure that the composite material has high strength and toughness while avoiding the negative effects of over-curing. The hot air circulation method is used to ensure that the composite material is heated evenly during the curing process. The function of hot air circulation is to transfer heat evenly to every part of the composite material through air convection, ensuring that all areas reach the required curing temperature in the same time, thereby achieving uniform curing and avoiding local overheating or insufficient curing. This method effectively reduces the internal stress of the material and improves the overall performance and reliability of the final composite material.
[0015] The present invention also provides an application method of the phosphogypsum composite nano adhesive material, wherein the composite material is used for: In the construction field, it is used as bonding material and repair material; In the field of environmental protection, it can be used as a cement substitute or pollutant adsorbent; In the field of high-performance composite materials, it is used as high-strength structural materials or high-temperature resistant materials.
[0016] The present invention provides a method for preparing a phosphogypsum composite nano adhesive material. The method has the following beneficial effects: 1. The present invention adopts the dual technology of ultrasonic dispersion and surface modification to make the nanoparticles evenly dispersed in the phosphogypsum matrix and avoid the agglomeration of particles. Thus, the mechanical properties of the composite material are improved, especially the compressive and tensile strength. Compared with the traditional simple mixing method, ultrasonic dispersion ensures the consistency and stability of material properties.
[0017] 2. The present invention ensures the temperature uniformity of the composite material during the entire curing process through hot air circulation curing technology. This technology solves the problem of uneven temperature difference in the traditional static heating curing process, improves the overall stability and strength of the material, and avoids the generation of cracks and bubbles.
[0018] 3. The present invention improves the adhesion and corrosion resistance of the composite material by optimizing the adhesive ratio and dispersant ratio. Compared with the existing formula with low adhesive dosage, this innovative improvement enhances the performance of the material in extreme environments, especially in terms of long-term corrosion resistance and high temperature resistance, providing more lasting protection.
[0019] 4. The innovative combination of surface-modified nanomaterials and high-performance adhesives in the present invention not only significantly improves the mechanical properties of the composite material, but also has excellent high temperature resistance and anti-aging capabilities. Compared with traditional methods, the material can still maintain high stability and toughness under high temperature and high load conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a process flow chart of the preparation method. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Please see attached Figure 1 : Example 1: Preparation of composite materials by modifying nano-silicon dioxide using a silanizing agent step: Take 70 parts of phosphogypsum powder, put it in an oven, and dry it at 60°C for 2 hours to ensure that the moisture content is less than 1%.
[0023] The dried phosphogypsum powder is crushed to below 200 mesh to ensure the uniformity of the particles.
[0024] Take 10 parts of nano-silica, add 3% volume concentration of 3-aminopropyltriethoxysilane (silanizing agent), and dissolve it in 90 ml of ethanol.
[0025] Using ultrasonic treatment, sonicate the nanosilica solution for 20 min with the power set at 150 W.
[0026] After ultrasonic treatment, the modified nano-silica was mixed with 70 parts of phosphogypsum powder in proportion.
[0027] Add 5 parts of epoxy resin modified adhesive and 1 part of silanizing agent (amino agent) as surfactant to ensure uniform dispersion.
[0028] 1 part of dispersant (polyvinyl alcohol) was added, and the mixture was treated with ultrasound for 15 minutes.
[0029] The mixture was poured into a mold and hot pressed with a set pressure of 3 MPa, a molding temperature of 100°C and a molding time of 60 min.
[0030] After molding, the composite material was allowed to cool naturally to 30°C for 2 hours.
[0031] Finally, the composite material was placed in a curing oven, the curing temperature was set to 90°C, the curing time was 3 hours, and hot air circulation heating was used to ensure uniform curing of the material.
[0032] Example 2: Enhancing the heat resistance of phosphogypsum composites Take 80 parts of phosphogypsum powder and dry it first to ensure that the moisture content is less than 1%.
[0033] The phosphogypsum powder is crushed to below 200 mesh and then sieved to remove large particles.
[0034] 8 parts of nano silicon nitride were added to ethanol at a concentration of 4%, and the surface was subjected to amino treatment.
[0035] The nano-silicon nitride was treated with an ultrasonic treatment device at a power of 200 W for 30 minutes to ensure uniform surface modification.
[0036] Mix nano silicon nitride and phosphogypsum powder evenly in a mass ratio of 7:80.
[0037] 5 parts of polyurethane adhesive were added to the mixture, and 1.5 parts of silanizing agent were added as a surfactant to ensure the dispersion of the nanoparticles.
[0038] 0.5 parts of sodium dodecylbenzene sulfonate was added as a dispersant and then processed by an ultrasonic disperser for 20 minutes to ensure uniform distribution.
[0039] The mixture was poured into a mold, the molding pressure was set to 1.5 MPa, the molding temperature was 90°C, and the molding time was 40 minutes.
[0040] After molding, cool to 30°C for 1.5 hours.
[0041] Curing stage: Place the material in the mold into a curing oven, control the temperature at 100°C, and cure for 2.5 hours. Use hot air circulation heating to ensure uniform curing.
[0042] Example 3: Preparation of high-strength phosphogypsum composite material Take 75 parts of phosphogypsum powder, dry it until the moisture content is less than 1%, and crush it to less than 200 mesh.
[0043] Take 12 parts of nano-silica, add 4% concentration of silanizing agent (3-aminopropyltriethoxysilane), and dissolve in ethanol.
[0044] Ultrasonic equipment was used to treat the nano-silica at a power of 180 W for 30 min to ensure that the modifier was evenly attached to the surface of the nano-silica.
[0045] The modified nano-silica was mixed with phosphogypsum powder in a ratio of 8:70.
[0046] Add 6 parts of epoxy resin adhesive and 1 part of aminating agent as a surfactant to the mixture to ensure uniform dispersion.
[0047] 1 part of dispersant (polyvinyl alcohol) was added and sonicated again for 15 min to ensure that all ingredients were evenly distributed.
[0048] The mixture was poured into a mold and the hot pressing molding conditions were set as follows: pressure 3 MPa, temperature 100°C, and time 60 minutes.
[0049] After molding, the mixture was cooled to 30°C for 2 hours.
[0050] Curing process: Place the composite material in a curing oven, set the curing temperature to 90°C, the curing time to 3 hours, and use hot air circulation to ensure uniform heating.
[0051] Example 4: Phosphogypsum composite material with enhanced corrosion resistance step: Take 70 parts of phosphogypsum powder, dry it until the moisture content is less than 1%, and then crush it to less than 200 mesh.
[0052] Take 6 parts of nano-silica, use 3% silanizing agent for surface modification, and use water as solvent.
[0053] Treat the nanosilica solution using an ultrasonic processor for 25 min with a power setting of 100 W.
[0054] Mix the modified nano-silicon dioxide and phosphogypsum powder in a ratio of 8:70.
[0055] 4 parts of epoxy resin adhesive and 1.5 parts of surfactant (silanizing agent) were added to ensure good dispersion of the nanoparticles.
[0056] 1 part of sodium dodecylbenzenesulfonate was added as a dispersant, and ultrasonic dispersion was continued for 10 minutes.
[0057] The mixture was placed in a mold and compression molded at a pressure of 1.5 MPa, a temperature of 80° C., and a time of 50 minutes.
[0058] After the molding is completed, the composite material is allowed to cool naturally to 30°C for 1 hour.
[0059] Curing treatment: Place the composite material in a curing oven, control the temperature at 110°C, cure for 4 hours, and use hot air circulation heating.
[0060] Comparative Example 1: Composite material without ultrasonic dispersion treatment Comparative Design: In this comparative experiment, we eliminated the step of ultrasonic dispersion in Example 1 and kept other conditions unchanged, in order to test whether ultrasonic dispersion affects the uniform dispersion of nanoparticles and the performance of the composite material.
[0061] Take 70 parts of phosphogypsum powder and dry it to ensure that the moisture content is less than 1%.
[0062] The dried phosphogypsum powder is crushed to below 200 mesh to ensure uniform particles.
[0063] Take 10 parts of nano-silica, add 3% volume concentration of 3-aminopropyltriethoxysilane, and dissolve it in 90 ml of ethanol.
[0064] Using conventional stirring instead of ultrasonication, manually stir the mixture for 20 minutes to ensure that the silanizing agent is attached.
[0065] The modified nano silicon dioxide is mixed with phosphogypsum powder in proportion.
[0066] Add 5 parts epoxy resin adhesive and 1 part silanizing agent (aminating agent), ensuring even dispersion.
[0067] 1 part of polyvinyl alcohol was added as a dispersant, and the mixture was mixed by ordinary stirring for 15 minutes.
[0068] The mixture was poured into a mold, the pressure was set to 3 MPa, the molding temperature was set to 100 °C, and the molding time was 60 min.
[0069] After molding, the mixture was cooled to 30°C for 2 hours.
[0070] Curing process: Place the composite material in a curing oven, set the curing temperature to 90°C, the curing time to 3 hours, and use hot air circulation.
[0071] Comparative Example 2: Composite material directly mixed without surface modification Comparative design: In this comparative experiment, we removed the surface modification step in Example 2 and directly used unmodified nano silicon nitride mixed with phosphogypsum, in order to compare the effects of surface modification on the mechanical properties and high temperature resistance of the material.
[0072] Take 80 parts of phosphogypsum powder, dry it until the moisture content is less than 1%, and then crush it to less than 200 mesh.
[0073] Take 8 parts of nano silicon nitride and mix them directly with phosphogypsum powder in proportion, skipping the surface amination treatment step.
[0074] 5 parts of polyurethane adhesive were added to the mixture, and 1 part of aminating agent was added as a surfactant.
[0075] 1 part of sodium dodecylbenzenesulfonate was added as a dispersant, and the mixture was treated with ultrasound for a further 15 minutes.
[0076] The mixture was poured into a mold, the molding pressure was set to 1.5 MPa, the molding temperature was 90°C, and the molding time was 40 minutes.
[0077] After the molding is completed, the composite material is allowed to cool naturally to 30°C for 1.5 hours.
[0078] Curing treatment: Place the composite material in a curing oven, control the temperature at 100°C, cure for 2.5 hours, and use hot air circulation.
[0079] Comparative Example 3: Curing without hot air circulation Comparative Design: In this comparative experiment, we removed the hot air circulation curing step in Example 3 and used a static heating method for curing, mainly to compare the effects of hot air circulation on curing uniformity and composite material performance.
[0080] Take 75 parts of phosphogypsum powder, dry it until the moisture content is less than 1%, and then crush it to less than 200 mesh.
[0081] Take 12 parts of nano-silica, add 4% concentration of silanizing agent (3-aminopropyltriethoxysilane), and dissolve in ethanol.
[0082] Using ultrasonic treatment, ultrasonicate the nanosilica solution for 30 min with the power set at 150 W.
[0083] The modified nano-silicon dioxide and phosphogypsum powder are mixed in a mass ratio of 7:70.
[0084] Add 6 parts of epoxy resin adhesive and 1 part of aminating agent as a surfactant to the mixture to ensure uniform dispersion.
[0085] 1 part of dispersant (polyvinyl alcohol) was added and sonicated for 15 min to ensure that all ingredients were evenly distributed.
[0086] The mixture was poured into a mold and the hot pressing molding conditions were set as follows: pressure 3 MPa, temperature 100°C, and time 60 minutes.
[0087] After molding, the mixture was cooled to 30°C for 2 hours.
[0088] During the curing process, the composite material is placed in a curing oven, the curing temperature is set to 90°C, the curing time is 3 hours, but hot air circulation heating is not used.
[0089] Comparative Example 4: Composite material with reduced adhesive ratio Comparative Design: This comparative experiment is based on Example 4, but the proportion of the modified adhesive is reduced, with the purpose of testing the effect of adhesive reduction on the corrosion resistance and overall mechanical properties of the composite material.
[0090] Take 70 parts of phosphogypsum powder, dry it to ensure that the moisture content is less than 1%, and crush it to less than 200 mesh.
[0091] Take 6 parts of nano-silica, use 3% silanizing agent for surface modification, and use water as solvent.
[0092] Treat the nanosilica solution using an ultrasonic processor for 25 min with a power setting of 100 W.
[0093] The modified nano-silica was mixed with phosphogypsum powder in a ratio of 8:70.
[0094] Add 3 parts of epoxy adhesive and 1.5 parts of surfactant (silanizing agent) to the mixture.
[0095] 1 part of sodium dodecylbenzenesulfonate was added as a dispersant, and ultrasonic dispersion was continued for 10 minutes.
[0096] The mixture was placed in a mold and compression molded. The pressure was set to 1.5 MPa, the molding temperature was 80°C, and the molding time was 50 minutes.
[0097] After the molding is completed, the composite material is allowed to cool naturally to 30°C for 1 hour.
[0098] Curing treatment: Place the composite material in a curing oven, control the temperature at 110°C, cure for 4 hours, and use hot air circulation heating.
[0099] Comparative experiment: Purpose of the experiment: This experiment aims to compare the effects of different process parameters in the examples and comparative examples on the performance of phosphogypsum composite nano-adhesive materials, especially the effects of surface modification, ultrasonic dispersion, and curing treatment on the mechanical properties and dispersibility of the materials.
[0100] Experimental Materials: Embodiment 1: phosphogypsum powder, surface-modified nano-silicon dioxide, epoxy resin adhesive, and polyvinyl alcohol dispersant.
[0101] Comparative Example 1: phosphogypsum powder, unmodified nano-silicon dioxide, epoxy resin adhesive, and polyvinyl alcohol dispersant.
[0102] Embodiment 2: phosphogypsum powder, surface-modified nano silicon nitride, polyurethane adhesive, and polyvinyl alcohol dispersant.
[0103] Comparative Example 2: phosphogypsum powder, unmodified nano silicon nitride, polyurethane adhesive, and polyvinyl alcohol dispersant.
[0104] Example 3: phosphogypsum powder, modified nano-silicon dioxide, epoxy resin adhesive, and hot air circulation curing.
[0105] Comparative Example 3: phosphogypsum powder, unmodified nano-silicon dioxide, epoxy resin adhesive, and static heating curing.
[0106] Example 4: phosphogypsum powder, modified nano-silicon dioxide, epoxy resin adhesive, and polyvinyl alcohol dispersant.
[0107] Comparative Example 4: The proportions of phosphogypsum powder, modified nano-silicon dioxide, epoxy resin adhesive and dispersant are reduced.
[0108] Preparation: According to the formulas of the embodiments and comparative examples, corresponding nanoparticles, phosphogypsum powder, adhesive and dispersant are prepared.
[0109] Surface modification: For nanoparticles that require surface modification, they were treated with a silanizing agent and processed by an ultrasonic disperser for 20 minutes at a power of 150W.
[0110] Mixing: Mix the surface-modified nanomaterials with phosphogypsum powder according to the proportion. Add epoxy resin adhesive and dispersant, and use ultrasonic treatment to further disperse the mixture to ensure the uniformity of the material.
[0111] Molding: Molding is carried out by compression molding or hot pressing technology, with a pressure of 1.5MPa to 3MPa, a temperature of 80℃ to 100℃, and a molding time of 30 to 60 minutes.
[0112] Curing: The example adopts hot air circulation curing, the temperature is controlled at 90°C, and the curing time is 3 hours. The comparative group uses static heating, the temperature is set at 90°C, and the curing time is also 3 hours.
[0113] Cooling: After molding, cool to room temperature. The cooling time is 1 to 2 hours.
[0114] Mechanical testing: Use a universal material testing machine to test tensile strength, compressive strength and flexural strength.
[0115] Corrosion resistance test: After the sample was placed in a salt spray chamber for 48 hours, the surface corrosion was observed using a scanning electron microscope (SEM).
[0116] Dispersion test: Use SEM to observe the distribution of nanoparticles in the composite material to ensure that there is no aggregation.
[0117] Comparative data table of performance of multiple composite materials By comparing the experimental results, it is known that the present invention adopts key process steps such as surface modification, ultrasonic dispersion, hot air circulation curing, etc., to improve the mechanical properties and uniformity of the composite material.
[0118] In Example 1, after the surface-modified nano-silicon dioxide was treated with ultrasound, the dispersibility of the particles was greatly improved, and the tensile strength, compressive strength and flexural strength of the composite material were all higher than those of the control group (Comparative Example 1). Through ultrasonic dispersion, the uniform distribution of nanoparticles avoids the problem of nanoparticle agglomeration in traditional methods, which plays a key role in improving the mechanical properties of the material.
[0119] The surface-modified nano silicon nitride in Example 2 has better dispersibility and interface bonding force than the nano silicon nitride without surface treatment (Comparative Example 2), and the heat resistance and mechanical properties of the composite material are improved. Through surface modification, a stronger interaction force is formed between the surface of the nano silicon nitride and the phosphogypsum matrix, which effectively improves the overall performance of the material, especially in terms of tensile strength and compressive strength, which is much better than the unmodified material.
[0120] In Example 3, hot air circulation curing improves the uniformity of the composite material and solves the problem of uneven curing caused by static heating curing (Comparative Example 3). The hot air circulation in the embodiment ensures uniform temperature distribution of the composite material throughout the curing process, avoiding bubbles and uneven curing caused by excessive temperature differences. In contrast, the static heating method in Comparative Example 3 leads to the formation of bubbles, affecting the stability and mechanical properties of the material.
[0121] In Example 4, although the same nano-silicon dioxide modification method and epoxy resin adhesive as in Example 3 were used, a polyvinyl alcohol dispersant was added and the proportion of the adhesive was increased, further improving the corrosion resistance of the composite material. In contrast, the amount of adhesive used in Comparative Example 4 was reduced, resulting in a decrease in the strength and corrosion resistance of the composite material, and some agglomeration of the nanoparticles in the material. This experimental result shows that increasing the amount of adhesive and optimizing the ratio of the dispersant play an important role in improving the overall mechanical properties and corrosion resistance of the material.
[0122] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A phosphogypsum composite nano adhesive material, characterized in that: The phosphogypsum composite nano adhesive material comprises the following components in parts by weight: Phosphogypsum powder: 70-90 parts; Nanomaterial: 5-15 parts, wherein the nanomaterial is nano silicon dioxide, nano silicon nitride or a combination thereof; Modified adhesive: 5-10 parts; Surfactant: 0.5-3 parts, the surfactant is a silanizing agent, an aminating agent or a combination thereof; Dispersant: 0.5 to 2 parts.
2. The phosphogypsum composite nano adhesive material according to claim 1, characterized in that: The modifier is a silanizing agent, and the reaction conditions are: The concentration of the silanizing agent is 2% to 5%; The reaction temperature is 25°C to 60°C; The reaction time is 1 to 3 hours; The solvent is ethanol or water.
3. A method for preparing a phosphogypsum composite nano adhesive material, characterized in that: Using the phosphogypsum composite nano adhesive material according to any one of claims 1 or 2 comprises the following steps: S1. Surface modification of nanomaterials; S2. pretreating phosphogypsum powder; S3, mixing the surface-modified nanomaterial with phosphogypsum powder, adhesive and other additives; S4, forming the mixture; S5. Curing the formed composite material.
4. The method for preparing a phosphogypsum composite nano-adhesive material according to claim 3, characterized in that: The surface modification of the nanomaterial includes: The nanomaterial is modified by using a modifier, wherein the modifier is a silanizing agent; Dissolve the nanomaterial and the modifier in an appropriate amount of solvent, and perform ultrasonic treatment to ensure that the modifier is evenly attached to the surface of the nanomaterial, wherein the ultrasonic dispersion time is 15 minutes to 30 minutes, and the ultrasonic power is 50W to 200W; The surface-modified nanomaterial is dried at a temperature ranging from 30° C. to 80° C. to remove excess solvent and unreacted chemicals.
5. The method for preparing a phosphogypsum composite nano-adhesive material according to claim 3, characterized in that: The pretreatment of the phosphogypsum powder comprises: Dry the phosphogypsum powder to ensure that its moisture content is less than 1%; The dried phosphogypsum powder is crushed to less than 200 meshes to increase its surface area; The crushed phosphogypsum powder is sieved to remove larger particles to ensure uniformity.
6. The method for preparing a phosphogypsum composite nano-adhesive material according to claim 3, characterized in that: The mixing process of the mixture comprises: The surface-modified nanomaterials are mixed with phosphogypsum powder in proportion; adding a modified adhesive and a surfactant to the mixture; adding a dispersant to enhance the dispersion of the nanomaterial in the mixture; The mixture is stirred by ultrasonic dispersion to make it evenly dispersed and ensure the uniform distribution of nanoparticles.
7. The method for preparing a phosphogypsum composite nano-adhesive material according to claim 3, characterized in that: The molding process comprises: After the mixture is poured into a mold, the mixture is molded by compression molding or hot pressing, wherein the compression molding pressure range is 0.5MPa to 2MPa, the hot pressing molding pressure range is 2MPa to 5MPa, the molding temperature range is 20°C to 120°C, and the molding time is 30 minutes to 90 minutes; The formed composite material is cooled to fix its shape.
8. The method for preparing a phosphogypsum composite nano-adhesive material according to claim 7, characterized in that: The cooling of the formed composite material comprises: Cooling temperature range: 25℃~40℃; Cooling time: 1 hour to 4 hours.
9. The method for preparing a phosphogypsum composite nano-adhesive material according to claim 3, characterized in that: The curing process comprises: placing the formed composite material in a curing oven for heating and curing; The curing temperature is controlled between 60℃ and 120℃; The curing time is controlled between 2 hours and 5 hours; The hot air circulation method is adopted to ensure that the composite material is heated evenly during the curing process.
10. A method for applying a phosphogypsum composite nano adhesive material, characterized in that: Use the phosphogypsum composite nano adhesive material according to any one of claims 1 or 2, wherein the composite material is used for: In the construction field, it is used as bonding material and repair material; In the field of environmental protection, it can be used as a cement substitute or pollutant adsorbent; In the field of high-performance composite materials, it is used as high-strength structural materials or high-temperature resistant materials.